Enhancing the Competence of Indonesian Military Observers in Addressing Assignment Challenges in the Minusca Mission in the Central African Republic - Handiana; Eko Setijo Pudjiantoro; Almuchalif Suryo (CV. Rayyan Dwi Bharata, 2026)
United Nations peacekeeping operations in the Central African Republic through the United Nations/Multidimensional Integrated Stabilization Mission in the Central African Republic (MINUSCA) require Military Observer (Milobs) to possess a high level of competence in dealing with a complex, dynamic, and multicultural operational environment. These competencies include technical skills, cross cultural communication, environmental adaptability, as well as analytical and decision-making abilities. In carrying out their duties, Milobs serve as observers, reporters, mediators, and liaisons among parties involved in conflict situations, making personnel readiness a critical factor for mission success. This study aims to analyze the implementation of pre-deployment training for Military Observer at the Indonesian Peacekeeping Mission Center (PMPP TNI) in enhancing personnel competence and readiness for deployment to MINUSCA. The study employed a qualitative method with a descriptive-analytical approach. Data were collected through interviews, observations, and document analysis. Informants consisted of training participants, instructors, training organizers, former Milobs, and currently deployed Milobs. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the pre deployment training conducted by PMPP TNI has been aligned with United Nations standards and has successfully developed the basic competencies required of Military Observers. However, a gap remains between the competencies provided during training and the operational requirements in MINUSCA, particularly in French language proficiency, cross-cultural communication, and adaptation to conflict dynamics. The integrated training program conducted in 2025 together with the Rapidly Deployable Battalion (RDB) and Engineering Company (Kizi) enhanced training realism and inter-unit coordination skills, but reduced the focus on Milob-specific competencies.This study concludes that the pre-deployment training program has established a solid foundation for competency development. Nevertheless, improvements are required in curriculum design, training methods, and context-based competency development tailored to mission-specific conditions in order to enhance the readiness and effectiveness of Indonesian Military Observers in supporting the success of United Nations peacekeeping operations.